Rewriting Elderly Self in Selected Contemporary Nepali Short Fiction - Phuyal, Komal Prasad (Perspectives on Higher Education, 2024)
Nepali short fiction has also rewritten the elderly self by depicting the protesting spirit in them. Even though old age is stereotypically believed to have been a time devoid of any possibility of agency, some contemporary authors have envisioned the resisting elderly self who attempts to rewrite the values of society. Such people have the power to challenge the deep-seated beliefs and ways of society. I have taken Mandira Madhushree's "Ambako Bot” [The Guava Tree] (2017), Bina Theeng’s “Aayam” [The Dimension] (2020), and Nayan Raj Pandey’s “Sarpadash” [The Snakebite] (2021) to analyze of the self of the central character in each of the stories. Madhushree presents an angry and frustrated old man who fells a ripe guava tree after his sons tell him that he cannot come to celebrate Dashain with him. The old man’s rage spills in the most unconventional ways: spiritually, he chops off the irresponsible branches emanating from his own body. Theeng’s central figure loses her son to a bike accident; still, she encourages her daughter-in-law to resettle herself. Pandey's hero charms the snakes and learns to live with the pains of life. He begins to redraw the boundary for himself by blurring the line between the real and the fantastic: he reinvents his dead daughter in the form of a phantom to accompany him. The old man takes a political bend in his course of action as he seeks revenge for the oppression imposed on the people on the whole. Madhushree, Theeng, and Pandey capture the changing ethos of time by showing the elderly people rewriting their self through dissent, protest, and resistance. This paper contends that Nepali fiction has reviewed modern Nepali elderly self by rewriting it in contemporary context as it analyzes the selected texts in the historical and sociological context of the changing times.